Modeling of polymerization of methyl methacrylate in homogeneous systems as a framework for processes improvements. - Intini, Antonio César de Oliveira (2019)
The polymerization of methyl methacrylate (MMA) was investigated in this dissertation. Selected kinetic models from the literature were reviewed, and two new, generalized models of diffusion-limited effects (gel- and glass effects), derived from the current models were proposed and tested for bulk and solution polymerization of MMA in batch and semi-batch reactors, under isothermal and non-isothermal conditions. The newly proposed models include the capability of modeling termination by combination, radical transfer to monomer and depropagation reaction. The new and previous models were compared with experimental data of bulk and solution polymerizations of MMA, under a selection of non-steady state processes conditions (initiator and monomer feed, step changes in temperature) and compositions (initiator and chain transfer agents, regarding both type and dosages). The particular case of a non-isothermal bulk polymerization was also investigated. A simulation program (Reactormodel) was developed in Matlab, and its algorithm is provided.